Trauma-Informed Practices in Early Childhood Education: Supporting Emotional Recovery and Classroom Reintegration After Disaster - Abdul Salam (Journal La Edusci, 2026)
Disasters disrupt not only children’s psychological security but also the stability of early learning environments. In early childhood education settings, post-disaster trauma may directly affect emotional regulation, classroom participation, and learning engagement. This study aimed to examine manifestations of trauma among children aged 3–6 years in a post-disaster context and to analyze how classroom-based psychosocial interventions support emotional stabilization and educational reintegration. A descriptive qualitative design was employed in a kindergarten functioning as a child-friendly psychosocial support setting. Data were collected through participatory classroom observation, semi-structured interviews with caregivers and educators, and children’s expressive activities, including drawing and symbolic play. Thematic analysis was conducted to identify patterns of trauma expression and changes in learning engagement. Findings indicate that trauma was primarily expressed through non-verbal behaviors, including regression, separation anxiety, sleep disturbances, hyperarousal, and reduced attention span, which interfered with structured classroom participation. Play-based and expressive strategies integrated into daily routines facilitated emotional regulation, peer interaction, and gradual re-engagement in learning activities. Recovery was most effective when family involvement and consistent caregiver–teacher collaboration supported classroom routines. The study highlights the importance of trauma-informed, developmentally appropriate practices embedded within early childhood education settings to promote both psychological recovery and educational continuity in post-disaster contexts.